EVALUASI PROGRAM BULAN IMUNISASI ANAK SEKOLAH (BIAS) DI DINAS KESEHATAN KOTA SURABAYA BERDASARKAN PENDEKATAN SISTEM - Eva Flourentina Kusumawardani; Mardi Fadillah; Laila Apriani Hasanah Harahap; Firman Firdauz Saputra; Meutia Paradhiba; Onetusfifsi Putra; Nasrianti Syam; Perry Boy Chandra Siahaan; Rubi Rimonda (Jurnal Kesehatan Tambusai, 2023)
The government is holding a School Child Immunization Month (BIAS) with the aim of protecting against diseases that can be prevented by immunization (PD3I) until school age. The background was when children enter elementary school age there was a decrease in the level of immunity obtained during immunization when infants. The research objective was a description of the BIAS program based on a systems approach (input, process and output) using a descriptive design. Data collection was carried out by means of in-depth interviews with a number of 3 (three) informants consisting of 1 (one) immunization program coordinator, 1 (one) head of surveillance and immunization section, and 1 (one) health information system employee. BIAS activity reports were reported in stages according to the data source (from the Puskesmas) to the District/City Health Office, then the District/City Health Office conducts analysis and interpretation of the data for the needs of the immunization program. The Surabaya City Health Office through the Health Information System (SIK) unit is the first door in the flow of data processing and analysis. The priority problem that needs to be resolved immediately was the availability of the School Children's Health Report Card, as a media for recording the results of health screening in school children in which there was an immunization variable. The health report card for school children was one of the media that can provide education about the health status of school children, in the development of changes to the schedule and types of immunization in the BIAS program, it was necessary to record and report the immunization status of school children in an orderly manner. Strong commitment across programs and across sectors in all lines of society so that the death rate from PD31 will decrease.